• Support PF! Buy your school textbooks, materials and every day products via PF Here!

Fourier series (sine,cosine)

  • Thread starter Kuma
  • Start date
134
0
1. The problem statement, all variables and given/known data

Given f(x) = 2x+1 periodic from -pi<x<pi. Find the fourier series from (-pi to pi) as well as the sine series from [0, pi] and cosine series from (0,pi)


2. Relevant equations



3. The attempt at a solution

So since f(x) is periodic it is odd, so then a0 and ak = 0.

for bk:

bk = 1/pi int f(x) sin kx from -pi to pi.
skipping forward, I get bk = [(-1)^ k][-4/k]

now im a bit confused about the sine and cosine series. I thought if f(x) was odd then it turns into a sine series automatically so isn't it basically the same thing as what I got?

And the cosine series should just be 0?
 

vela

Staff Emeritus
Science Advisor
Homework Helper
Education Advisor
14,328
1,046
So since f(x) is periodic it is odd, so then a0 and ak = 0.
f isn't odd. For example, f(1) = 3 while f(-1) = -1. Clearly, f(1) ≠ -f(-1).

now I'm a bit confused about the sine and cosine series. I thought if f(x) was odd then it turns into a sine series automatically so isn't it basically the same thing as what I got?

And the cosine series should just be 0?
The idea is to restrict f to the domain [0, π] and then extend it so that it's an even or odd function on the interval [-π, π]. In other words, when -π≤x<0, you have f(x) = ±f(|x|).
 
134
0
f isn't odd. For example, f(1) = 3 while f(-1) = -1. Clearly, f(1) ≠ -f(-1).


The idea is to restrict f to the domain [0, π] and then extend it so that it's an even or odd function on the interval [-π, π]. In other words, when -π≤x<0, you have f(x) = ±f(|x|).
I thought when you have f(x+p) when its periodic it is just equal to f(x)?
Regardless I got ak and a0 as 0 even when I used f(x) = 2x+1

And shouldn't it be f(x) = f(-x)?

if x E [0,pi] then f(x) = 2x +1 and if x E [-pi,0], f(-x) = 2x+1??
 
Last edited:

vela

Staff Emeritus
Science Advisor
Homework Helper
Education Advisor
14,328
1,046
I thought when you have f(x+p) when its periodic it is just equal to f(x)?
If p is the period, then yes. But what does that have to do with anything about f being even or odd?

Regardless I got ak and a0 as 0 even when I used f(x) = 2x+1
All I can say is you got the wrong answer since you haven't shown your work.

And shouldn't it be f(x) = f(-x)?
Yes, if f is an even function.

if x E [0,pi] then f(x) = 2x +1 and if x E [-pi,0], f(-x) = 2x+1??
No, that's not right. Take ##x=+\pi/2 \in [0,\pi]## so ##f(\pi/2) = \pi+1##. Now take ##x=-\pi/2 \in [-\pi,0]##. You're saying ##f(-x) = 2x+1##, but you have
$$f(-x) = f(-(-\pi/2)) = f(\pi/2) = \pi+1$$ whereas
$$2x+1 = 2(-\pi/2) + 1 = -\pi + 1.$$ Clearly, f(-x) ≠ 2x+1.
 
134
0
Ok I figured it out. For the fourier series I got ak and a0 as 0? But for the cosine series i did this
F(x) = f(x) for 0<x<pi
F(x) = -f(-x) for -pi<x<0

where f(x) = 2x+1

that results in an even function so I solved for a0 and ak from there.
 

vela

Staff Emeritus
Science Advisor
Homework Helper
Education Advisor
14,328
1,046
How are you getting a0=0 for the regular Fourier series?
 
134
0
Oh yeah I made a calculation error i believe.

ao = 1/2pi int from pi to -pi 2x+1 dx
= 1/2pi (x^2 + x) from pi to -pi
= 1/2pi [pi^2 + pi - ((-pi)^2 -pi]
= 1

ak = 1/pi int 2x+1 cos kx dx from -pi to pi

u = 2x+1 dv = cos kx
du = 2 dx v = 1/k sin kx

x from -pi to pi
=1/pi[(2x+1 sin kx)/k) - 2/k int (sin kx) from -pi to pi]

= 1/pi[0 - 2/k (-1/k cos kx from -pi to pi)]
= 1/pi[2/k^2 (cos kx from -pi to pi)] = 0

that right?
 

vela

Staff Emeritus
Science Advisor
Homework Helper
Education Advisor
14,328
1,046
Looks good.
 

Physics Forums Values

We Value Quality
• Topics based on mainstream science
• Proper English grammar and spelling
We Value Civility
• Positive and compassionate attitudes
• Patience while debating
We Value Productivity
• Disciplined to remain on-topic
• Recognition of own weaknesses
• Solo and co-op problem solving
Top